The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1965
DOI: 10.1016/0016-6480(65)90081-x
|View full text |Cite
|
Sign up to set email alerts
|

Steroid production by incubated mouse adrenals

Abstract: The meuse adrenal is more responsive to ACTH than the rat adrenal.The meuse adrenal does not differentiate between concentrations of ACTH in solution, only between total amounts. ACKNOWLEDGEMENTS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1965
1965
1975
1975

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 39 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have already shown that calcium is needed for optimal steroid production and release in vitro (Birmingham et at. 1960;Triller & Birmingham, 1965), and it has been suggested from studies on broken cell preparations, which do not respond to ACTH, that the action of calcium is to promote the intramitochondrial synthesis of corticosteroids (see Peron & McCarthy, 1968). However, the present studies on intact glands show that in the absence of extracellular calcium, ACTH is still able to increase steroidogenesis, although steroid output is markedly depressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have already shown that calcium is needed for optimal steroid production and release in vitro (Birmingham et at. 1960;Triller & Birmingham, 1965), and it has been suggested from studies on broken cell preparations, which do not respond to ACTH, that the action of calcium is to promote the intramitochondrial synthesis of corticosteroids (see Peron & McCarthy, 1968). However, the present studies on intact glands show that in the absence of extracellular calcium, ACTH is still able to increase steroidogenesis, although steroid output is markedly depressed.…”
Section: Discussionmentioning
confidence: 99%
“…In light of the presumed absence of secretary granules within cortical cells, the findings by Birmingham and her associates (Birmingham, Kurlents, Lane, Muhbstock & Traikov, 1960;Triller & Birmingham, 1965), that calcium is important for optimal steroid production and output from sectioned adrenal glands in response to ACTH and 3'5'-AMP, is of great interest. The present experiments explore the role of calcium in ACTHevoked corticosteroid release from isolated perfused adrenal glands, in order to gain further insight into the nature of the action of calcium in the adrenal cortex and to understand more about the intimate mechanism by which calcium acts in the physiological process of secretion.…”
Section: Introductionmentioning
confidence: 99%